Discourse of Renewal in Government Institutions (Study of Crisis Communications on Flood Problems Facing Dki Province) - Nur Halsha Damira Putri (Budapest International Research and Critics University, 2022)
As the capital city of the Republic of Indonesia, Jakarta continuously carries out development in various fields, including infrastructure development as one of the most massive fields. However, the development was not able to cover several issues in Jakarta. One of the most complaint-generated issues is flooding. The magnitude and intensity of the floods that occur almost every year makes a lot of media coverage to see the performance of the DKI Jakarta Provincial Government. This paper discusses how the DKI Jakarta Provincial Government, under the leadership of Basuki Tjahaja Purnama (BTP/Ahok) in dealing with floods using the Discourse of Renewal theory. This theory does not take crisis as something negative, instead, it considers crisis as an opportunity for the organization to make better performance. This study seeks to find out the implementation of the crisis communication strategy by the DKI Jakarta Provincial Government under Ahok's leadership and its impact on improving the image of the institution. This study uses a qualitative research method with a case study approach that aims to understand and explore crisis communication strategies in more depth. The collected data is then analyzed in five stages, starting from framing, labeling, summarising, synthesizing, and concluding. Based on the results of the research, BTP/Ahok's leadership style, which was bold and decisive in dealing with floods, has brought newness to the organization. The novelty is considered effective, as evidenced by the results of the Indo Barometer survey which named BTP/Ahok as the governor who successfully handled floods.